Immunodeficiency: when T cells are stuck at home - Hogquist, Kristin A. (2008)
A flurry of recent studies has suggested the importance of the actin regulator coronin-1A in lymphocyte development. Now, mutations in this regulator are shown to cause immunodeficiency in both mice and humans.